Identifying Pore Type of Lagoon and Barrier Carbonate to Model Shear Wave Velocity in Salawati Basin by Differential Kuster-ToksÖz - Wulandari, Yulia Putri; Rosid, Mohammad Syamsu (POSITRON, 2023)
The shape of pores in sedimentary rocks is dependent on the geometric structure of the rock matrix grains. Carbonate rocks have more complex pore types compared to clastic due to the effects of diagenesis and the depositional environment. The study analyzed the deposition of Kais carbonate in barrier and lagoon environments. It categorized the pores into inter-particle, moldic/vuggy, and micro-cracks. The type of pore in a rock is directly related to its stiffness and shear resistance, which influences its shear wave velocity (Vs). Thus, a higher shear modulus leads to a higher Vs value. Reservoir characterization heavily relies on the Vs data. However, this data is limited to the observed area. Therefore, Vs modeling is a more effective and efficient approach. The modeling will conduct thoroughly with the identification of the pore type. The rocks moduli are calculated by the pore inclusion method using the differential Kuster-Toksöz (DKT) equation and defining the aspect ratio, reflecting the pore type. The YP-1 well has barrier carbonate, while YP-2 and YP-3 have lagoon carbonate with inter-particle as the primary pore type. Micro-cracks on top of Kais are present. YP-4 and YP-5 have similar proportions of micro-cracks and inter-particle as dominant pore types. The predicted Vs and measured logs strongly correlate with an R2 value above 0.8. The Vs value range for micro-cracks is 2,300 ft/s to 6,000 ft/s, and for inter-particle, it is 6,000 ft/s to 8,500 ft/s. Pore types above 8,500 ft/s are very stiff (moldic pore type).